Penerapan Model Pembelajaran Problem Based Learning Dalam Meningkatkan Critical Thingking Siswa Pada Pembelajaran Fiqih - Salwa, Firda; El-Yunusi, M. Yusron Maulana; Sholehuddin, H.M. (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This study aims to describe the application of the Problem Based Learning (PBL) learning model in improving students' critical thinking skills in fiqh subjects at SMA Islam Parlaungan Waru Sidoarjo. The research used a qualitative approach with descriptive methods. Data collection techniques include observation, interviews, and documentation. The results showed that the application of PBL was carried out through several stages: orienting students to the problem, organizing to analyze, finding solutions, and developing and evaluating results. This model proved effective in improving three main aspects of students' critical thinking, namely the ability to distinguish fact and fiction, distinguish constructive and destructive criticism, and the ability to make decisions from the results of problem solving. In addition, the application of PBL also provides space for students to actively discuss, enrich literacy, and develop self-confidence. Supporting factors for the successful implementation of this model include teacher readiness, adequate learning media and learning environment support. However, there were also obstacles such as time constraints and differences in student characters. In general, PBL is effective in fostering students' critical thinking, especially in understanding and applying fiqh material contextually